Prevention of Antibiotic-associated Diarrhea in Children with Lactobacillus Probiotic - O. V. Molochkova; O. V. Kladova; A. A. Novokshonov; N. L. Waltz; Yu. V. Kompaniets; N. L. Grishkevich (Детские инфекции (Москва))
The data on the frequency of the spread of antibiotic-associated diarrhea (AAD) in children. A different incidence of AAD in children of different age groups, highest in children under the age of 3 years.The possibility of reducing the frequency of its development when administered prophylactically domestic probiotic containing Lactobacillus — Acipol on the background of antibiotic therapy. Prophylactic Acipol can reduce the incidence of AAD in these patients is 21%, and reduce the duration and severity of diarrheal syndrome.